The Neglected Place of “Totems” in Contemporary Art - Aixin Zhang (Religions, 2023)
The religious nature of Joseph Beuys’ works was ignored or intentionally avoided by mainstream criticism since his artistic practice was ridiculed for its potential spirituality. It is argued that Beuys’ works are work meditations on the issues of potential ego in totemic art, which are frequent topics of theological concern. For example, what is the nature of our consciousness after death, and how does it relate to the consciousness of others? Beuys’ conceptual artworks reveal his engagement with the “witchcraft etiquette” of totemic art and his exploration of theological questions such as the relation between human consciousness and divinity, the role of sacrifice and resurrection, and the meaning of self-awareness. In other words, we can draw inspiration from the theological theories of Alfred North Whitehead and Georg Wilhelm Friedrich Hegel to examine Beuys’ choice of conceptual art through the lens of his deep self-consciousness of totem worship. In general, Beuys’ works pose an important question: how can we awaken our chaotic consciousness to new or forgotten sprouts which may rejuvenate our existence in the world?